Destructive Upper Airway Disease from Eosinophilic Granulomatosis with Polyangiitis (EGPA): The Very First Case. (23rd May 2019) - Saha, Biplab; Saha, Aditi; Cordeiro-Rudnisky, Fernanda; Shkolnik, Boris; Beegle, Scott
Abstract : Eosinophilic granulomatosis with polyangiitis (EGPA) is a multisystem vasculitic disorder that predominantly affects medium- and small-sized blood vessels. EGPA belongs to a group of vasculitides known as anti-neutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV). Upper airway involvement is seen in all ANCA-associated vasculitides, but destructive upper airway disease has never been reported in patients with EGPA. We report the first case of erosive chondritis and saddle nose deformity in a 50-year-old patient suffering from EGPA.